Risk–Benefit Assessment of Consumption of Rice for Adult Men in China - Fang, Haiqin; Zhang, Quantao; Zhang, Shengjie; Zhang, Tongwei; Pan, Feng; Cui, Yufeng; Thomsen, Sofie Theresa; Jakobsen, Lea S.; Liu, Aidong; Pires, Sara M. (Frontiers in Nutrition, 2021)
Objective: To evaluate the health impact of current and alternative patterns of rice consumption in Chinese adult men (40–79 years of age). Methods: We applied a risk–benefit assessment (RBA) model that took into account the health effects of selenium (Se), cadmium (Cd), and inorganic arsenic (i-As). The health effects included the prevention of prostate cancer associated with exposure to Se, and an increased risk of lung, bladder, and skin cancer for i-As and chronic kidney disease (CKD) for Cd. We defined the baseline scenario (BS) as the current individual mean daily consumption of rice in the population of interest and two alternative scenarios (AS): AS1 = 50 g/day and AS2 = 200 g/day. We estimated the health impact for different age groups in terms of change in Disability-Adjusted Life Years (ΔDALY). Results: The BS of rice consumption was 71.5–105.4 g/day in different age groups of adult men in China. We estimated that for AS1, the mean ΔDALY was −2.76 to 46.2/100,000 adult men of 40–79 years old. For AS2, the mean ΔDALY was 41.3 to 130.8/100,000 individuals in this population group. Conclusion: Our results showed that, based on associated exposure to selenium, cadmium, and i-As in rice, the current consumption of rice does not pose a risk to adult men in China. Also, a lower (50 g/day) or higher (200 g/day) rice consumption will not bring larger beneficial effects.